Menemukan Suara Hati Melalui Eksplorasi Gaya Bahasa Unik dari Lirik Lagu Wildflower Karya Billie Eilish - Ghaitsa Najwa Rasiyah; Desilva Aulia Azzahra (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The lyrics of the song that will be discussed in this study are Wildflower which is a pop song created by Billie Eilish which was released on May 17 2024 in her third studio album, Hit Me Hard and Soft. This song tells the story of Billie's experience of initially comforting a girl who is heartbroken after a breakup, but then she actually has a relationship with the girl's ex-lover. The purpose of this study is to describe the language style contained in the lyrics of the Wildflower song and explain the meaning of the language described. This research is qualitative research. The research for this study is to use data analysis, namely listening to the song to be analyzed, understanding the content of the lyrics, then looking for words that contain majas or language style. The method used is qualitative descriptive. The data of this study is an analysis of the use of metaphor, personification, repetition, hyperbole, and irony language styles contained in the lyrics of the Wildflower song. The results of this study show that there is the use of metaphor, personification, repetition, hyperbole, and irony language styles in the lyrics of Wildflower songs.